The Nutritive Value of Aquatic Plants and their Utilization in Fish and Animal Feed - Bahnasy, Soheir; Kamel, Gamal; Saaffan, Samia (Arab Journal for Sciences and Research Publishing, 2016)
Using of dried aquatic plants as daily protein to animal and fish was the topic of investigation in this study. Analyses of different plants (water hyacinth, duckweed and lotus) in Laboratory. This is to evaluate their potentials in animal and feed composition.The proximate analysis shows that the moisture content ranged from 6.25% in the plant to 32.5% for the crude lipids, the least value of 2.5 to 5.4 in the whole plant while the percentage crude fiber ranged from 4.5 to 11.1% in the whole plant. The percentage crude protein ranged from 8.55% to 14.2 %. In the whole plant duckweed plant is conceder the prefer plant can used as nutritive source of animal and fish feed then water hyacinth and lotus. Total amino acid are large amount in water hyacinth than lotus and duckweed (397.638, 175.98 and 95.915 mg/g).
Keywords: water hyacinth; duckweed; lotus; mutative value; protein; amino acid